1
$\begingroup$

How do I negate the following statement?

What are the steps which should be taken to negate an argument such as the one given?

$$\exists y \forall x ((y > 0) \land (x < y))$$

$\endgroup$

closed as off-topic by user21820, user91500, JonMark Perry, Antonios-Alexandros Robotis, José Carlos Santos Aug 10 '17 at 9:56

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – user21820, user91500, JonMark Perry, Antonios-Alexandros Robotis, José Carlos Santos
If this question can be reworded to fit the rules in the help center, please edit the question.

1
$\begingroup$

Remember, when you negate a predicate, you negate "each part of it". It's like the negation distributes.

Some rules are: $$\neg\exists=\forall, \neg\forall=\exists,\neg(\lor)=\land, \neg(\land)=\lor,\neg P=\neg P$$ Therefore, distribute the $\neg$ $$\neg(\exists y \forall x ((y > 0) \land (x < y)))\iff \forall y\exists x(\neg((y > 0) \land (x < y))$$

Now, $\neg(y\gt 0)=(y\leq 0)$, "if its not greater, then it must be less than or equal to"

Similarly, $\neg(x<y)=(x\geq y)$

Finishing out negation off, we get:

$$\iff\forall y \exists x ((y\leq 0)\lor(x\geq y))\text{ notice $\land$ changes to $\lor$}$$

$\endgroup$
  • $\begingroup$ Question, how come the negative of $\forall$ isn't "none"? $\endgroup$ – Andrew Tawfeek Aug 9 '17 at 3:34
  • 1
    $\begingroup$ Consider $P(x):\text{ x is a boy}$. This means, "all $x$ are boys". Negating it, we see, "not all $x$ are boys". If not all of them are boys, there are definitely some that are boys, hence the $\exists$ $\endgroup$ – K Split X Aug 10 '17 at 14:25
  • $\begingroup$ Ahhh that makes things clear, thank you! $\endgroup$ – Andrew Tawfeek Aug 10 '17 at 14:26
  • $\begingroup$ Your welcome @AndrewTawfeek $\endgroup$ – K Split X Aug 10 '17 at 15:44
3
$\begingroup$

Essentially the $\forall$ becomes $\exists$ and vice-versa, and $\land$ becomes $\lor$. Hence, we have: $$\begin{align}\lnot\left(\exists y\forall x((y>0)\land(x<y))\right)&\iff\forall y\exists x(\lnot(y>0)\lor\lnot(x<y))\\&\iff\forall y\exists x((y\leq 0)\lor(x\geq y))\end{align}$$

$\endgroup$
  • $\begingroup$ Hi Dave, thanks for the answer. Just a question, why does > become <= instead of <? $\endgroup$ – Oliver K Aug 9 '17 at 4:46
  • $\begingroup$ Because $>$ does not allow for $=$, so the opposite of $>$ is either $<$ or $=$, and hence, $\leq$. $\endgroup$ – Dave Aug 9 '17 at 10:56
-1
$\begingroup$

Theorem. The negation of $$\exists y \forall x ((y > 0) \land (x < y))$$ is $$\forall y \exists x ((y \le 0) \lor (x \ge y))$$

Proof. By Lemma 1, 2, 3, 4, and 5.

Lemma 1. The negation of $\exists y~ P(y)$ is $\forall y,~\lnot P(y)$

Proof. Calling $Y$ the universe $$\exists y~ P(y)\equiv\exists y\in Y,~ P(y)\equiv Y\cap P\neq\emptyset$$ where $P=\{z|~P(z)\}$.

So its negation is: $$Y\cap P=\emptyset\equiv Y\subset P^c\equiv\forall y\in Y,~\lnot P(y)$$ where $P^c=\{z|~\lnot P(z)\}$

Lemma 2. The negation of $\forall y~ P(y)$ is $\exists y,~\lnot P(y)$

Proof. Calling $Y$ the universe $$\forall y~ P(y)\equiv\forall y\in Y,~ P(y)\equiv Y\subset P$$

So its negation is: $$Y\not\subset P\equiv Y\cap P^c\neq\emptyset\equiv\exists y\in Y,~\lnot P(y)$$

Lemma 3. The negation of $a\land b$ is $\bar a\lor\bar b$

Proof. By de Morgan $$a\land b=\overline{\bar a\lor\bar b}$$

Lemma 4. The negation of $y>0$ is $y\le 0$

Proof. Here it is understood that $y\in \mathbb{R}$, though not explicitly stated. $$y>0\equiv y\in\{z|~z>0\}$$ So its negation is $$y\not\in\{z|~z>0\}\equiv y\in\{z|~z>0\}^c$$ where $\{z|~z>0\}^c=\mathbb{R}\setminus\{z|~z>0\}=\{z|~z\le0\}$

Lemma 5. The negation of $x<y$ is $x\ge y$

Proof. Here it is understood that $x,~ y\in \mathbb{R}$, though not explicitly stated. $$x<y\equiv (x,y)\in\{(w,z)|~w< z\}$$ So its negation is $$(x,y)\not\in\{(w,z)|~w< z\}\equiv y\in\{(w,z)|~w< z\}^c$$ where $\{(w,z)|~w< z\}^c=\mathbb{R}^2\setminus \{(w,z)|~w< z\}=\{(w,z)|~w\ge z\}$

$\endgroup$

Not the answer you're looking for? Browse other questions tagged or ask your own question.